ANALYSIS OF NOSTALGIC LEXICAL UNITS FROM A LINGUOCULTURAL PERSPECTIVE (Scientific journal of the Fergana State University, 2025)
This article examines the linguocultural characteristics of nostalgic lexical units. The linguistic representation of nostalgia is associated with national memory, cultural heritage, and personal experiences, manifesting differently across languages. The study conducts a comparative analysis of the semantic and pragmatic features of nostalgic lexical units in Uzbek and English, highlighting their role in national identity and cultural encoding. In Uzbek, nostalgic lexicon is predominantly linked to collective memory and cultural values, whereas in English, it is primarily based on individual experiences and personal emotions. The article employs methods of linguocultural analysis, semantic analysis, and comparative linguistics to explore the manifestation of the nostalgia phenomenon within the language system.